The effect of neuroscientific evidence on sentencing depends on how one conceives of reasons for incarceration. - Annalise Perricone; Arielle Baskin-Sommers; Woo-Kyoung Ahn (PLoS ONE, 2022)
Neuroscientific evidence is increasingly utilized in criminal legal proceedings, prompting discussions about how such evidence might influence legal decisions. The effect of neuroscientific testimony on legal decisions remains uncertain, with some studies finding no effect, others reporting that neuroscience has a mitigating impact, and some indicating neuroscience evidence has an aggravating effect. The present study attempts to explain these divergent findings by showing that the effect of neuroscience evidence on sentencing interacts with beliefs about the goals of the criminal legal system. Using a between-subjects design, participants (N = 784) were asked to assume different rationales for imprisonment, before receiving neuroscientific evidence about antisocial behavior and its potential relation to the defendant. Participants recommended a sentence for the defendant prior to and after reading the neuroscientific evidence. Participants who were given the rationale of retribution as the primary goal of imprisonment significantly decreased their sentencing recommendations. When the goal of imprisonment was to protect the public from dangerous people, participants provided longer post-testimony sentences. Lastly, when the goal was to rehabilitate wrongdoers, participants also increased sentences from pre to post. Thus, the impact of neuroscientific evidence is not monolithic, but can lead to either mitigated or aggravated sentences by interacting with penal philosophy.